Hubungan Religiusitas dan Interaksi Teman Sebaya dengan Perkembangan Moral Siswa Sekolah Menegah Atas Tarbiyah Islamiah Hamparan Perak - Agus Sutiono; Nur Aini; Abrar Parinduri (Mahesa Research Center, 2022)
This article aims to examine the relationship between religiosity and peer interaction with the moral High School Students Tarbiyah Islamiah Hamparan Perak. This study uses a quantitative approach with multiple regression analysis analysis techniques. The population of this research is 140 students. The sampling technique used is purpsosive sampling, by taking a sample of 5% of the population so that the sample is 110 students and 30 students are experimental. This study uses three scales, namely the scale of religiosity, the scale of peer interaction and the scale of moral development. This study concludes (1) The existence of a positive and significant correlation between religiosity and moral development with (rx1y) of 0.541 means that it shows that religiosity contributes to moral development by 54.1%. (2) The existence of a positive and significant relationship between peer interaction and moral development with (rx1y) of 0.533 means that it shows a contribution to moral development of 54.1%. (3) There is a positive relationship between religiosity and peer interaction on moral development with a linear estimation regression equation model Y=77.762+0.216X1+0.340X2, which means that when these two variables are combined, they both contribute and significantly influence moral development